Access to treatment for Hepatitis C among injection drug users: results from the cross-sectional HOPE IV study - Kyriakos Souliotis; Eirini Agapidaki; Manto Papageorgiou; Niki Voudouri; Xenophon Contiades (BMC, 2017)
Abstract Background Evidence suggests that Greece is among the European countries with increased trend in HCV prevalence among injecting drug users (IDUs) from 2008 to 2014. Nonetheless, the access of IDUs to treatment for Hepatitis C Virus (HCV) is very limited while the risk of co-infection and transmission remains high. In an effort to better understand the inhibitors to HCV treatment, the present study aimed to investigate the main barriers to access in a sample of IDUs. Methods The cross-sectional study was carried out between July and September 2015 using a 23-items questionnaire. Participants were recruited from urban primary services, mobile health vans, community health services, day-care centers as well as during street work, located in Athens, Greece. Inclusion criteria were age above 18 years, understanding and speaking Greek sufficiently, HCV diagnosis, intravenous drug use. Data collection was carried out by health professionals of Praksis, a non-governmental organization. For the comparisons of proportions chi-square and Fisher's exact tests were used. Results The study sample consisted of 101 HCV patients, 68% male. More than 80% of study participants experienced barriers in accessing their doctor and medication during the past 12 months. The most common obstacles in accessing a doctor were "delay in making the appointment and "difficulties in going to the doctor due to health condition or lack of means of transport". Access to physician or medication was not differed according to gender, but significant differences were found according to economic status and health insurance coverage. 56.1% of participants reported loss or treatment delay due to barriers to treatment. The majority of participants had deteriorated financial status, health status, access to health services and medication, higher financial burden for health services, worse mental health and lower adherence to medical instructions in 2015 compared to 2009. Conclusions The findings from the present study revealed that the vast majority of IDUs experience significant barriers in seeking HCV care in Greece, thus highlighting the need for immediate action in this particular area due to the high risk of co-infection and transmission.